Experimental infection of Peste des Petit Ruminant virus and Mannheimia haemolytica A2 in goats: immunolocalisation of Mannheimia haemolytica antigens - Obukowho Emikpe, Benjamin; Mohd Yusoff, Md Sabri; Stephen O., Akpavie; Saad, Mohd Zamri (Elsevier Science Publishers, 2010)
Nigerian strain of Peste des Petit Ruminant (PPR) virus and Mannheimia haemolytica (MH) biotype A serotype 2, was used successfully to reproduce a concurrent disease in West African Dwarf goats. The development of the various pathological features were studied at regular intervals following infection. The acute inflammatory reaction which had developed by day 3 after initial infection was characterised by flooding of the alveoli by neutrophils, oedema, hemorrhage and syncytial cells together with a moderate bronchial and bronchiolar epithelial necrosis. This progressed to a milder acute broncho interstitial pneumonia with giant cells. At this stage, the mucosal immunity were well developed especially the aggregate form of NALT and more of nodular forms of BALT. The organisms were demonstrated with strong immunostaining in the necrotic center, necrotic alveolar wall, fibrin, serous exudate, and degenerated leukocyte in the alveoli and respiratory airways. The bacterial antigens were observed as a strong immunostaining in the blood vessels of the nasal septum, sinusoid in the liver and interstium of the kidney, cytoplasm of alveolar macrophages, pneumocytes, bronchial and bronchiolar epithelium, in the monocytes in the blood vessels. These findings confirmed the enhancement of MH tropism especially in the respiratory tract, liver and kidney. It also showed that West african dwarf goats are highly susceptible to the intratracheal combined infection of PPR virus and MH. The fact that the infection induces strong mucosal responses, this phenomenon can be explored in Africa with the use of combined PPR virus and MH intranasal vaccines to curtail the menace of pneumonia associated with the combined infection on field.